Józef Hen o Polsce Żydów polskich, której już nie ma, ale wciąż jest (Nowolipie, 1991) - Gosk, Hanna (Załącznik Kulturoznawczy, 2022)
The article discusses Nowolipie – an autobiographical work written by Józef Hen. This prose is a kind of a journey into the past to resurrect and to commemorate it for the author himself and for others. Hen successfully achieves in this text the present of the past effect (R. Koselleck’s term). The analysis presents an interesting interweaving of three narrative layers: the first is focused on the pre-war present of Nowolipie (a part of Warsaw area), the second is connected with the shadow of the Shoah, and the third deals with the self-presentation of the author – a writer and a Polish Jew.